Association between depression and anxiety scores and inflammation in patients with isolated coronary artery ectasia - Ahmet Seyfeddin Gürbüz; Yakup Alsancak; Beyza Saklı; Mehmet Akif Düzenli (KARE Publishing, 2019)
Objective: Depression and anxiety disorders are frequently found in combination with obstructive coronary artery disease. Coronary artery ectasia (CAE) is an atypical form of coronary artery disease, the etiology of which has not yet been clearly defined. The aim of this study was to assess the existence of a relationship between anxiety/depression and CAE. Methods: A CAE group (n=41; mean age: 58.9+-9.0 years) and a control group (n=42; mean age: 58.0+-9.6 years) were compared. The anxiety and depression status of patients was evaluated using the Hospital Anxiety and Depression Scale (HADS) questionnaire. Results: Age, sex, ejection fraction, and cardiovascular risk factor data were similar in both groups. The serum Creactive protein (CRP) and uric acid levels as well as the leukocyte count were significantly higher in the CAE group (p<0.05). The HADS anxiety score was higher in the CAE group, but without statistical significance (p=0.23). The HADS depression score and total HADS score was significantly higher in the CAE group (p<0.001 and p<0.001). The total HADS score and the HADS depression score were correlated with the serum CRP level (r=0.489; p<0.001 and r=0.543; p<0.001, respectively), whereas the anxiety score was not correlated with CRP (r=0.85; p=0.23). Conclusion: The depression score, CRP, and uric acid levels were greater in patients with isolated CAE compared with those of patients with normal coronaries. The anxiety score did not demonstrate a relationship to CAE; however, there was an association between the depression score and CRP, which is an inflammatory marker.